Geographical distribution of Viperidae, Elapidae and Hydrophidae in Costa Rica - Taylor, Richard T. (1973)
During the past three years the Instituto Clodomiro Picado has collected 2090 specimens of venomous snakes belonging to the Viperidae, Elapidae, and Hydrophidae families. Careful records of the places of capture were kept to map the geographical distribution. Our data present sorne discrepancies with those of other authors.